Queerness in Play (Cham : Springer International Publishing, 2018)
Queerness in Play examines the many ways queerness of all kinds-from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum-intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games-as a culture, an industry, and a medium-help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games.
1. Queer Game Studies: Young But Not New (Todd Harper, Meghan Blythe Adams, and Nicholas Taylor) -- Part 1: Queer Foundations -- 2. Queer(ing) Game Studies: Reviewing Research on Digital Play and Non-normativity (Sarah Evans) -- 3. Envisioning Queer Game Studies: Ludology and the Study of Queer Game Content (Evan W. Lauteria) -- Part 2: Representing Queerness -- 4. The Representation (or the Lack of It) of Same-sex Relationships in Digital Games (Yowei Kang and Kenneth C. C. Yang) -- 5. Affliction or Affection: The Inclusion of a Same-sex Relationship in The Last of Us (Daniel Sipocz) -- 6. What if Zelda Wasn't a Girl? Problematizing Ocarina of Time's Great Gender Debate (Chris Lawrence) -- 7. Maidens and Muscleheads, White Mages and Wimps, From the Light Warriors to Lightning Returns (Mark Filipowich) -- 8. The Big Reveal: Exploring (Trans)Femininity In Metroid (Evelyn Deshane and R. Travis Morton) -- 9. Bye, Bye, Birdo: Heroic Androgyny and Villainous Gender Variance in Video Games (Meghan Blythe Adams) -- Part 3: Un-Gendering Assemblages -- 10. Cues for Queer Play: Carving a Possibility Space for LGBTQ Role-Play (Tanja Sihvonen and Jaakko Stenros) -- 11. 'Sexified' Male Characters: Video Game Erotic Modding for Pleasure and Power (Nathan Thompson).-12. Let's Come Out! On Gender and Sexuality, Encouraging Dialogue and Acceptance (Maresa Bertolo, Ilaria Mariani, and Clara Gargano) -- Part 4: No Fear of a Queer Planet: Gaming and Social Futures -- 13. Outside the Lanes: Supporting a Non-normative League of Legends Community (Nick Taylor and Randall Hammond).-14. The Abject Scapegoat: Boundary Erosion and Maintenance in League of Legends (Elyse Janish) -- 15. Out on Proudmoore: Climate Issues on an MMO (Carol A. Stabile and Laura Strait).
Literature, Cultural and Media Studies
text file PDF
Keywords: Culture-Study and teaching; Culture; Technology; Gender; Digital media; Communication; Popular Culture